Maintaining Integrity Under Stress: Envelope Stress Response Regulation of Pathogenesis in Gram-Negative Bacteria - Hews, Claire L.; Cho, Timothy; Rowley, Gary; Raivio, Tracy L. (Frontiers in Cellular and Infection Microbiology, 2019)
The Gram-negative bacterial envelope is an essential interface between the intracellular and harsh extracellular environment. Envelope stress responses (ESRs) are crucial to the maintenance of this barrier and function to detect and respond to perturbations in the envelope, caused by environmental stresses. Pathogenic bacteria are exposed to an array of challenging and stressful conditions during their lifecycle and, in particular, during infection of a host. As such, maintenance of envelope homeostasis is essential to their ability to successfully cause infection. This review will discuss our current understanding of the σE- and Cpx-regulated envelope stress responses (ESRs), with a specific focus on their role in the virulence of a number of model pathogens.